The use of strategic bombing against non-state actors in the Middle East: Objectives and limitations of air power in the cases of Hezbollah, Houthis & ISIS - Aly, Basem Osama (AUC Knowledge Fountain, 2016)
This thesis examined both the rationale and objectives of states in resorting to air power in contemporary, asymmetrical conflicts in the Middle East, focusing on the three cases of aerial operations on Hezbollah in Lebanon, ISIS in Syria, and the Houthi rebels in Yemen. The thesis concluded that states adopt post-heroic military policies that prioritize avoiding casualties among the ranks of their armed forces, which carries a series of negative consequences on achieving the objectives of the war, especially amid limited or no backing by ground and naval troops.